2011
DOI: 10.1080/10255842.2010.493885
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of cross-country skiing

Abstract: A program for numerical simulation of a whole ski race, from start to finish, is developed in MATLAB. The track is modelled by a set of cubical splines in two dimensions and can be used to simulate a track in a closed loop or with the start and finish at different locations. The forces considered in the simulations are gravitational force, normal force between snow and skis, drag force from the wind, frictional force between snow and ski and driving force from the skier. The differential equations of motion ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…However, in the simulation it is beneficial to solve the motion equations in the same global directions at every point along the course (Carlsson et al 2011). Therefore, equations of motion are transformed to the global -and -coordinates.…”
Section: Derivation Of the Equations Of Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the simulation it is beneficial to solve the motion equations in the same global directions at every point along the course (Carlsson et al 2011). Therefore, equations of motion are transformed to the global -and -coordinates.…”
Section: Derivation Of the Equations Of Motionmentioning
confidence: 99%
“…Mathematical modeling of a ski race, combined with efficient nonlinear optimization routines, provides a tool for analyzing how these efforts should be best distributed. Carlsson et al (2011) showed how numerical simulations in cross-country skiing can be performed in order to calculate the total race time for an arbitrary athlete. The simulation model solves the equations of motion for constant time steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This acceleration was estimated from the measured speed as an average between the measured values. The OP estimate is based on the numerical optimization model of Sundström et al [11] which is based on the same mechanical model as Carlsson et al [12]. The OP estimate uses the method of moving asymptotes [13] and varies the power output to minimize the square of speed difference between the mechanical model and the actual performance of a cross-country skier on a treadmill.…”
Section: Power Output Estimatesmentioning
confidence: 99%
“…The evaluation model is based on the same numerical simulation approach as the OP estimate [12]. The STT was simulated by solving the motion equation of roller skiing with the power output estimates as input data.…”
Section: Evaluation Modelmentioning
confidence: 99%